2020
DOI: 10.1037/neu0000621
|View full text |Cite
|
Sign up to set email alerts
|

Narrative video scene description task discriminates between levels of cognitive impairment in Alzheimer’s disease.

Abstract: The process of interpreting and acting upon the visual environment requires both intact cognitive and visual systems. The narrative description (ND) task, initially developed to detect changes in ecologically relevant visual function in people with impaired vision, is an objective measure of the ability to perceive, understand, and describe a visual scene in a movie clip. Objective: Because the ND task draws heavily on semantic and working memory ability in addition to basic visual perception, we aimed to asse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 45 publications
0
13
0
Order By: Relevance
“…NLP also has many applications in other fields. Taking the medical industry as an example, NLP technology detects signs of cognitive impairment by analyzing the conversations between the elderly and patients with Alzheimer [7]. In the banking industry, optical character recognition (OCR) and NLP technologies are used to automatically capture key document text and perform document content reviews to speed up the lending process [8].…”
Section: Introductionmentioning
confidence: 99%
“…NLP also has many applications in other fields. Taking the medical industry as an example, NLP technology detects signs of cognitive impairment by analyzing the conversations between the elderly and patients with Alzheimer [7]. In the banking industry, optical character recognition (OCR) and NLP technologies are used to automatically capture key document text and perform document content reviews to speed up the lending process [8].…”
Section: Introductionmentioning
confidence: 99%
“…IA scores tended to decrease with increasing importance of nature (B = −0.09; 95% CI = −021 to 0.01; z = 1.86; P = 0.06) and tended to increase with increasing importance of man-made objects (B = 0.24; 95% CI = 0.04 to 0.43; z = 2.39; P = 0.02). In an in-person study, Reeves et al 34 found similar effects, with man-made object importance increasing, and nature importance decreasing IA scores. The other content-related factors (importance of faces, human figures, or auditory content, or the number of cuts per clip, or lighting level) were not significant ( P > 010) so they were removed from the model.…”
Section: Resultsmentioning
confidence: 83%
“…Previously, we have found that IA scores can vary with age, education, gender 4,29,31,32 and with MoCA score in a study of participants with Alzheimer's disease. 32 We accepted p ≤ 0.01 as statistically significant, and report terms with 0.10 ≥ p > 0.01 as trends.…”
Section: Statistical Analysesmentioning
confidence: 92%
“…We have used this method to demonstrate impaired video comprehension due to defocus blur, 31 CVL, 4 hemianopia 29 and Alzheimer's disease. 32 In the present study, we examined the effect of Bubble Magnification on gaze behaviour and video comprehension in individuals with CVL. We hypothesised that: (1) participants with CVL would look at the Bubble Magnification, and thus their gaze coherence (measured as normalized scanpath saliency, NSS 27 ) would improve and (2) Bubble Magnification would improve video comprehension (measured as IA score 31 ).…”
Section: Introductionmentioning
confidence: 99%